2006
DOI: 10.1037/0033-3204.43.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Changes in male partner abuser attachment styles in group treatment.

Abstract: This study examined attachment pattern change of partner violent men over the course of 17 weeks of integrated cognitive-behavioral/psychodynamic group treatment. Results indicated a significant increase in the number of men reporting a secure attachment from pre- to posttreatment. Subsequent analysis indicated that secure-changed men reported significant increases in comfort with closeness and depending on others from pre- to posttreatment. From pre- to posttreatment, insecure and secure-unchanged men reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
3
30
0
3
Order By: Relevance
“…Si bien los autores proponen que los hombres que han ejercido violencia pueden presentar apego seguro (Holtzworth-Munroe et al, 2003;Holtzworth-Munroe & Stuart, 1994;Lawson et al, 2006;Waltz et al, 2000), en la investigación de Buck et al (2014) los porcentajes fluctúan entre un 15 y un 27% como máximo. Los datos en Chile reportan un 21,7% (Barría Muñoz, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Si bien los autores proponen que los hombres que han ejercido violencia pueden presentar apego seguro (Holtzworth-Munroe et al, 2003;Holtzworth-Munroe & Stuart, 1994;Lawson et al, 2006;Waltz et al, 2000), en la investigación de Buck et al (2014) los porcentajes fluctúan entre un 15 y un 27% como máximo. Los datos en Chile reportan un 21,7% (Barría Muñoz, 2013).…”
Section: Discussionunclassified
“…Loinaz, Echeburúa y Ullate (2012) plantean que la evaluación del apego forma parte de los protocolos que se utilizan con los hombres violentos con la pareja, para diferenciar subtipos de agresores (Amor, Echeburúa & Loinaz, 2009;Babcock et al, 2000;Dutton, 2008;Holtzworth-Munroe et al, 2000;Holtzworth-Munroe & Stuart, 1994) o para evaluar resultados terapéuticos (Lawson, Barnes, Madkins & Francois-Lamonte, 2006). Sin embargo, la mayoría de los estudios se ha centrado en hombres en reclusión carcelaria y orientados a la tipificación de los agresores (Dutton, 2008(Dutton, , 2011Echeburúa et al, 2009;Feeney, 1999;Jacobson & Gottman, 1998/2001Loinaz et al, 2012).…”
Section: Apego Y Violenciaunclassified
“…The studies that adopted intervention models different from the cognitive behavioural, the psychoeducational or the combination of both 25,43,53 , revealed positive results. For instance, the study of Lawson et al 43 , that employed an intervention program based on cognitive behavioural and psychodynamic models, showed an increase in attachment and in global functioning and a decrease in anxiety and depressive symptoms and in violence against the partner or ex-partner.…”
Section: Methods and Program Efficacymentioning
confidence: 99%
“…In fact, these results are consistent with Arias et al 18 findings, showing that programs based on intervention models different from Duluth and cognitive-behavioural have a significantly positive effect. However, it is important to note that some of the programs included in the present analysis also integrate strategies from cognitive-behavioural models 43,54 . Additionally, some of these studies revealed other weaknesses: small sample dimentions 43 , research design 26,30,33,34,39,64 and sample specificities 50,54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation